1998
DOI: 10.1093/emboj/17.12.3372
|View full text |Cite
|
Sign up to set email alerts
|

PRAK, a novel protein kinase regulated by the p38 MAP kinase

Abstract: L.New and Y.Jiang contributed equally to this workWe have identified and cloned a novel serine/ threonine kinase, p38-regulated/activated protein kinase (PRAK). PRAK is a 471 amino acid protein with 20-30% sequence identity to the known MAP kinase-regulated protein kinases RSK1/2/3, MNK1/2 and MAPKAP-K2/3. PRAK was found to be expressed in all human tissues and cell lines examined. In HeLa cells, PRAK was activated in response to cellular stress and proinflammatory cytokines. PRAK activity was regulated by p38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
332
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(348 citation statements)
references
References 71 publications
14
332
2
Order By: Relevance
“…Here we have presented in vitro evidence for the participation of two novel stress-activated protein kinases, i.e. PRAK (New et al 1998) and MSK1 (Deak et al 1998) in the regulation of TH. These kinases are expressed in numerous human tissues, including heart, lung, placenta, liver, kidney, pancreas, muscle and brain, with the highest levels found in pancreas, muscle and brain (Deak et al 1998;New et al 1998).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Here we have presented in vitro evidence for the participation of two novel stress-activated protein kinases, i.e. PRAK (New et al 1998) and MSK1 (Deak et al 1998) in the regulation of TH. These kinases are expressed in numerous human tissues, including heart, lung, placenta, liver, kidney, pancreas, muscle and brain, with the highest levels found in pancreas, muscle and brain (Deak et al 1998;New et al 1998).…”
Section: Discussionmentioning
confidence: 98%
“…PRAK (New et al 1998) and MSK1 (Deak et al 1998) in the regulation of TH. These kinases are expressed in numerous human tissues, including heart, lung, placenta, liver, kidney, pancreas, muscle and brain, with the highest levels found in pancreas, muscle and brain (Deak et al 1998;New et al 1998). Furthermore, using an MSK1 specific antibody, we have by western blotting confirmed that MSK1 is present in mouse adrenal glands and bovine adrenal medulla (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MNK1 is another kinase substrate of p38 whose function is thought to reside in translational initiation due to the observation that MNK1 and MNK2 can phosphorylate eukaryotic initiation factor-4e (eIF-4E) [59,60]. p38 regulated/activated kinase (PRAK) is a p38α and/or p38β activated kinase that shares 20-30% sequence identity to MK2 and is thought to regulate heat shock protein 27 (HSP27) [61]. Mitogen-and stress-activated protein kinase-1 (MSK1) can be directly activated by p38 and ERK, and may mediate activation of CREB [62][63][64].…”
Section: Downstream Substrates Of P38 Group Map Kinases Protein Kinasmentioning
confidence: 99%
“…Our previous results have pointed out the complexity of the MAP kinase signaling pathway, which is due to the fact that each individual MAP kinase can be activated by two or three upstream MAP2Ks and multiple MAP3Ks in Drosophila under different stimuli (Zhuang et al, 2006). Upon activation, p38 can phosphorylate and activate a number of transcription factors including ATF-2/ATF-7, CHOP/GADD153, Elk1, MEF2-C, Sap1 and CREB (Wang et al,1996;Raingeaud et al,1996;Han et al,1997;Iordanov et al,1997;Whitmarsh et al,1997;Shivers et al, 2010), and protein kinases such as MAPKAPK2, MNK, PRAK, MSK1 and RSK-B (Stokoe et al,1992;Fukunaga et al,1997;Waskiewicz et al,1997;New et al,1998;Deak et al,1998;Pierrat et al,1998), thus eliciting different cellular responses.…”
Section: Introductionmentioning
confidence: 99%